Evidence‐based guideline for the diagnosis and treatment of Mycoplasma pneumoniae pneumonia in children (2023) - The Subspecialty Group of Respiratory, the Society of Pediatrics, Chinese Medical Association; China National Clinical Research Center of Respiratory Diseases; Editorial Board, Chinese Journal of Pediatrics (Pediatric Investigation)
ABSTRACT Mycoplasma pneumoniae pneumonia (MPP) is the most common atypical pneumonia among children, with non‐specific clinical manifestations. Despite various laboratory diagnostic methods, the diagnostic criteria remain inconsistent, potentially leading to missed or overdiagnosis. The incidence of severe and refractory cases of MPP is increasing, and there are issues with non‐standard treatment in clinical practice. To standardize the diagnosis and treatment of MPP in Chinese children, the Subspecialty Group of Respiratory, the Society of Pediatrics, Chinese Medical Association, China National Clinical Research Center of Respiratory Diseases and the Editorial Board of Chinese Journal of Pediatrics jointly established a guideline expert group to formulate the “Evidence‐Based Guideline for the Diagnosis and Treatment of Mycoplasma Pneumoniae Pneumonia in Children (2023)” based on both domestic and international research findings.